2017
DOI: 10.1039/c6ta10755a
|View full text |Cite
|
Sign up to set email alerts
|

Capacity retention of lithium sulfur batteries enhanced with nano-sized TiO2-embedded polyethylene oxide

Abstract: DFT and in situ SERS revealed that the shuttle mechanism and Li anode passivation are suppressed by preferential nano-sized TiO2/polysulfide adsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…3,40,65 Furthermore, several studies in the field of Li/S battery research demonstrated that polysulfides can be dissolved in PEO, showing high mobility in Li/S cells with SPEs. [66][67][68] It can therefore be assumed that removal of the LSPS decomposition products, i.e., of Li-ions and polysulfides, into the polymer is a driving force for the oxidation of LSPS, following the principle of Le Chatelier.…”
Section: Discussionmentioning
confidence: 99%
“…3,40,65 Furthermore, several studies in the field of Li/S battery research demonstrated that polysulfides can be dissolved in PEO, showing high mobility in Li/S cells with SPEs. [66][67][68] It can therefore be assumed that removal of the LSPS decomposition products, i.e., of Li-ions and polysulfides, into the polymer is a driving force for the oxidation of LSPS, following the principle of Le Chatelier.…”
Section: Discussionmentioning
confidence: 99%
“…These oxide nanoparticles can interact with oxygen atoms in PEO chains thus reducing crystallization of PEO chains. TiO 2 nanoparticles in PEO‐bases SPEs can improve performance of Li–S cells ( Figure a) . The DFT calculations and Raman measurements revealed that the interaction between TiO 2 nanoparticles and polysulfide intermediates can alleviate the polysulfide shuttle.…”
Section: Solid‐state Electrolytesmentioning
confidence: 97%
“…Schematic illustration of the inhibition of soluble Li 2 S n diffusion upon charging. Reproduced with permission . Copyright 2017, Royal Society of Chemistry.…”
Section: Solid‐state Electrolytesmentioning
confidence: 99%
“…This is because the unique structure of PEO-Al 2 O 3 -based SPE allows the free transport of lithium ions and prevents the transport of polysulfide anions through the physical absorption and electrochemical deposition, which can effectively reduce the shuttle effect and the loss of active materials . Bing-joe Hwang et al also added TiO 2 to the PEObased solid electrolyte improving the performance of the battery effectively (Lee et al, 2017) (Figure 3A). The specific capacity of the polymer electrolyte with nano-sized TiO 2 is >1,450 mAh g −1 , and the capacity retention after 100 cycles is 87%.…”
Section: Li-s Batteries Based On Solid Polymer Electrolytementioning
confidence: 99%